Mentalizing in clinical practice - Allen, Jon G.; Fonagy, Peter 1952-; Bateman, Anthony 1952- (American Psychiatric Publ., 2008)
Introduction -- Mentalizing -- Development -- Neurobiology -- The art of mentalizing -- Mentalizing interventions -- Treating attachment trauma -- Parenting and family therapy -- Borderline personality disorder -- Psychoeducation -- Social systems
Includes bibliographical references and index
Keywords: Psychotherapie; Psychotherapy; Mental healing; Self-perception; Awareness; Psychotherapy / methods; Psychoanalytic Theory; Social Behavior; Social Perception; Online-Ressource; Mentalisierung; Selbstbeobachtung